Transforming Food Systems: The Missing Pieces Needed to Make Them Work. Issue 1 (10th December 2020) - Kennedy, Eileen; Webb, Patrick; Block, Steven; Griffin, Timothy; Mozaffarian, Dariush; Kyte, Rachel
ABSTRACT: Food systems lie squarely at the intersection of several overarching goals of the UN and member states, as embodied in the Sustainable Development Goals, including eliminating poverty, hunger, and malnutrition in all its forms, achieving good health and well-being, while promoting environmental sustainability. The need for radical transformation of current food systems is inescapable if the world is to achieve one, let alone all, of these goals. Meeting this challenge will inevitably be disruptive to current food systems, carry costs, and be politically onerous. But the projected benefits far outweigh these difficulties. This commentary spells out the complexity of issues that need to be tackled to design and implement food systems that improve diets, nutrition, and health in an equitable fashion, while simultaneously respecting planetary boundaries. Six critical domains are identified that must be addressed for the successful transformation of food systems: 1 ) reinvent agriculture, 2 ) transform food environments for healthy diets, 3 ) mitigate climate change, 4 ) productively engage the private sector, 5 ) influence public policy priorities, and 6 ) establish true cost accounting of food. Because science is crucial for each of these domains, a research-driven strategy, emphasizing a collaborative process, is outlined. Bold, new, but technically and politically feasible actions are needed to effectively transform current food systems.